2014
DOI: 10.1016/j.solidstatesciences.2013.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Sr1−xBaxSnO3 system applied in the photocatalytic discoloration of an azo-dye

Abstract: Semiconductor materials have received substantial attention as photocatalysts for controlling water pollution. Among these materials, perovskite-structured SrSnO 3 is a promising candidate for this application, whereas BaSnO 3 exhibits very low activity. In the present work, Sr 1-x Ba x SnO 3 (x = 0, 0.25, 0.50, 0.75 and 1) was synthesized by solid-state reaction and was applied in the photocatalytic discoloration of the organic dye Remazol Golden Yellow. The perovskite structure was obtained for all compositi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
32
0
14

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 56 publications
(60 reference statements)
4
32
0
14
Order By: Relevance
“…Some of these works reported the use of alkaline earth stannates in water splitting [5,13,14], whereas others applied these materials for dye photodegradation, [9,12]. For instance, Sales et al [15] synthesized Sr 1-x Ba x SnO 3 powders and observed that the photodegradation of remazol golden yellow is strongly influenced by the composition of the photocatalyst. In a recent study, Moshtaghi et al [16] investigated the photodegradation of acid blue 92 and acid black 1 using SrSnO 3 as the photocatalyst and obtained discoloration percentages larger than 93%.…”
Section: Introductionmentioning
confidence: 99%
“…Some of these works reported the use of alkaline earth stannates in water splitting [5,13,14], whereas others applied these materials for dye photodegradation, [9,12]. For instance, Sales et al [15] synthesized Sr 1-x Ba x SnO 3 powders and observed that the photodegradation of remazol golden yellow is strongly influenced by the composition of the photocatalyst. In a recent study, Moshtaghi et al [16] investigated the photodegradation of acid blue 92 and acid black 1 using SrSnO 3 as the photocatalyst and obtained discoloration percentages larger than 93%.…”
Section: Introductionmentioning
confidence: 99%
“…This dye is commonly used in the textile industry for dyeing cellulose fibers. The removal of Remazol Yellow Gold RNL from aqueous solutions has been accomplished by adsorption [17], anaerobic degradation [18] and photocatalytic approaches [19].…”
Section: Introductionmentioning
confidence: 99%
“…9 To maximize the use of sunlight, photocatalysts with the perovskite (ABO 3 ) structure have been recently exploited as highly effective photocatalysts. Several researchers have employed different strategies to solve this problem, such as the partial substitution 11 and nitrogen doping of A or B ions, 12 coupling with semiconductors, 13 or modication with noble metals. Several researchers have employed different strategies to solve this problem, such as the partial substitution 11 and nitrogen doping of A or B ions, 12 coupling with semiconductors, 13 or modication with noble metals.…”
Section: Introductionmentioning
confidence: 99%